Capture and translocation of a rod-like molecule by a nanopore: orientation, charge distribution and hydrodynamics. Issue 11 (4th March 2022) - Qiao, Le; Slater, Gary W.
Abstract : We investigate the rod orientation during translocation with electrohydrodynamics included using hybrid Langevin dynamics and lattice Boltzmann simulations. Abstract : We investigate the translocation of rods with different charge distributions using hybrid Langevin dynamics and lattice Boltzmann (LD–LB) simulations. Electrostatic interactions are added to the system using the P 3 M algorithm to model the electrohydrodynamic interactions (EHI). We first examine the free-solution electrophoretic properties of rods with various charge distributions. Our translocation simulation results suggest that the order parameter is asymmetric during the capture and escape processes despite the symmetric electric field lines, while the impacts of the charge distribution on rod orientation are more significant during the capture process. The capture/threading/escape times are under the combined effects of charge screening, rod orientation, and charge distributions. We also show that the mean capture time of a rod is shorter when it is launched near the wall because rods tend to align along the wall and hence with the local field lines. Remarkably, the orientational capture radius we proposed previously for uniformly charged rods is still valid in the presence of EHI.